TAURIYAH DALAM AL-QUR’AN : PENGERTIAN, MACAM, DAN CONTOHNYA - Faliha Aulia Siregar; Lira Zufika Simamora (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
This study discusses the concept of tauriyah in the Qur’an, including its definition, classifications, and examples found in Qur’anic verses. Tauriyah is one of the branches of Arabic rhetoric (balaghah) that employs words containing two meanings: a close meaning that is easily understood and a distant meaning that represents the intended message. This research aims to explain the essence of tauriyah as a rhetorical style in the Qur’an and to identify its various forms in the interpretation of verses. The study uses a qualitative method with a library research approach by analyzing Qur’anic commentaries, rhetoric books, and other relevant literature. The findings indicate that tauriyah in the Qur’an plays an important role in enhancing the beauty of linguistic structure while deepening the meaning of the verses. The types of tauriyah include mujarradah, murasyyah, mubayyanah, and muhayyah’ah, each having distinct characteristics based on the relationship between the close and distant meanings contained in a word. Examples of tauriyah in the Qur’an demonstrate the eloquence of Arabic rhetoric, which not only possesses literary value but also strengthens the moral and spiritual messages of the Qur’anic verses. Therefore, this study confirms that tauriyah is one of the evidences of the linguistic miracle of the Qur’an in terms of rhetoric and meaning.